Microwave Extraction of Essential Oils from Jasminum Sambac Flowers - Osman, Nurshahidah (2006)
The Microwave Extraction System (MES) is a high-speed method used to extract target compounds from various raw materials. It was originally developed for the extraction of flavors and fragrances from plant materials, which is generally carried out by conventional techniques that require a lot of energy or a long time or a combination of both. In this study, a microwave extraction system (MES) is developed for the extraction of essential oils from Jasminum sambac flowers. The important MES process parameters, i.e, time, temperature and microwave power are controlled to obtain rapidly the highest quantity and quality of oil. The performance of MES is compared with the Conventional Extraction Method (CEM) using various methods such as dry distillation (DD), wet distillation (WD), hydro distillation (HD) and steam distillation (SD) in terms of rapidity, quality and percentage of yield, chemical composition of oil and its efficiency. The MES is performed by DD and WD at irradiation power of about 450 W and temperature about 100 oC for 1 hour whereas CEM is performed by HD and SD at extraction power of 450 W and temperature 100 oC for 8 hours. The absorption power of microwave irradiation by Jasminum sambac flowers are predicted for DD and WD. The project has successfully proved that MES is more efficient than CEM in terms of rapidity, quality and quantity of yield, energy use, easiness in operation and cost effectiveness. The MES provides a rapid extraction, with about 8 times faster than CEM. After 1 hour of microwave extraction, it is possible to collect sufficient essential oil which provides comparable yields to those obtained with 8 hours by CEM. Using MES, DD requires only 5 minutes to obtain its first oil droplet and WD requires 8 minutes whereas using CEM, both HD and SD allows 15 and 42 minutes respectively to obtain the first oil droplet. DD requires less time to obtain its first oil droplet compared to other methods because the absorption power for dry sample is higher than for wet sample. The DD technically gives higher percentage yield with 0.10 % which is about 5 times higher compared to SD and HD where both only contribute 0.02 %, respectively whereas WD contributes 0.06 %. Although more compounds are detected in the essential oil extracted by CEM, substantial higher amounts of highly odoriferous compounds are present in the MES extract. The relative amount of oxygenated fraction in essential oil is less than 30 % for CEM and more than 30 % for MES. In terms of the energy consumed, the energy consumption in MES is 8 times lower than in CEM. HD requires heating of 0.4 liter of water and 200 g of flowers to the extraction temperature, and evaporating the water and essential oil for 8 hours whereas DD only requires heating 200 g of fresh flowers and evaporating the in situ water and essential oil of the plant material for 1 hour. Furthermore, MES requires maximum power irradiation only to heat up the sample and water to its boiling point and thus obtain its first oil droplet whereas CEM requires maximum power irradiation throughout the process. Essentially, the MES provides an easily controlled system, rapid extraction process; high yield and purity extracts, more valuable essential oils, extracts with chemical compositions comparable to conventional method and allows a substantial saving of energy. These advantages not only reduce operating costs, but also result in a more environmentally friendly process.